2002
DOI: 10.1063/1.1469692
|View full text |Cite
|
Sign up to set email alerts
|

Effect of carbazole–oxadiazole excited-state complexes on the efficiency of dye-doped light-emitting diodes

Abstract: Interactions between hole-transporting carbazole groups and electron-transporting 1,3,4-oxadiazole groups were studied by photoluminescence and electroluminescence ͑EL͒ spectroscopy, in blends of poly͑N-vinylcarbazole͒ with 2-tert-butylphenyl-5-biphenyl-1,3,4-oxadiazole ͑PVK:PBD͒ and in random copolymers with carbazole and oxadiazole groups attached as side chains. Different excited-state complexes form in the blends, which exhibit exciplexes, and in the copolymers, which manifest electroplexes, due to topolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
68
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 117 publications
(71 citation statements)
references
References 46 publications
3
68
0
Order By: Relevance
“…This indicates that PBD is not an electron acceptor which would quench the PL emission of PVK. Formation of exciplexes in PVK-PBD (40 wt %) films was observed by several groups using steady state and time-resolved photoluminescence spectroscopy [10,22,23]. Negres et al…”
Section: Photoluminescence and Electroluminescencementioning
confidence: 99%
See 1 more Smart Citation
“…This indicates that PBD is not an electron acceptor which would quench the PL emission of PVK. Formation of exciplexes in PVK-PBD (40 wt %) films was observed by several groups using steady state and time-resolved photoluminescence spectroscopy [10,22,23]. Negres et al…”
Section: Photoluminescence and Electroluminescencementioning
confidence: 99%
“…The EL spectra for the PVK-PBD blends have dominant peak at 430 nm, which is red-shifted by ca 5 nm in comparison to the PL spectrum; this effect is explained by formation of the exciplex states. It was also shown that the EL spectra have some long-wavelength contribution dependent on composition of the blends and on applied electric field [4,10].…”
Section: Introductionmentioning
confidence: 99%
“…1) were synthesized according to known procedures. 10,11 Azobis(isobutyronitrile) (AIBN) was recrystallized from methanol and stored in the freezer. All the other chemicals and solvents were used as received from Aldrich (Steinheim, Germany).…”
Section: Methodsmentioning
confidence: 99%
“…The emission for mixtures of PVK with the similar hole transport compound 2-͑4-biphenylyl͒-5-͑4-tert-butylphenyl͒-1,3,4-oxadiazole ͑PBD͒ has previously been assigned to an exciplex formed between a hole on PVK and an electron on PBD. 11 The addition of FIrpic to our PVK-OXD7 device results in blue emission, with a maximum in the EL spectrum at 480 nm together with a shoulder at about 505 nm. This emission is similar to that reported previously for FIrpic doped into PVK, 3,12 and is also characteristic of the emission observed when FIrpic is mixed in other host matrices, e.g., 4, 4Ј-bis͑9-carbozolyl͒-2, 2Ј-biphenyl ͑CBP͒, 13 4, 4Ј-bis͑9-carbazolyl͒-2, 2Ј-dimethylbiphenyl ͑CDBP͒, 8 or mCP.…”
Section: Methodsmentioning
confidence: 99%